2013
DOI: 10.1073/pnas.1320528110
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of usher pore gating in Escherichia coli pilus biogenesis

Abstract: Extracellular fibers called chaperone-usher pathway pili are critical virulence factors in a wide range of Gram-negative pathogenic bacteria that facilitate binding and invasion into host tissues and mediate biofilm formation. Chaperone-usher pathway ushers, which catalyze pilus assembly, contain five functional domains: a 24-stranded transmembrane β-barrel translocation domain (TD), a β-sandwich plug domain (PLUG), an N-terminal periplasmic domain, and two Cterminal periplasmic domains (CTD1 and 2). Pore gati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…Also within the translocation domain are a hairpin loop between β-strands 5 and 6 (the β5-6 hairpin), which dips toward the barrel lumen, and the only α-helix in the translocation domain, which caps the β5-6 hairpin from the extracellular side. These two elements are believed to confer stability to the surrounding region, particularly to the plug domain, as their removal causes increased pore permeability (Volkan et al, 2013), channel opening (Mapingire et al, 2009) and decreased interactions between conserved residues (Farabella et al, 2014). Specific communities of amino acids in the α-helix and the β5-6 hairpin were proposed to function in the transmission of a putative allosteric signal that triggers plug displacement (Farabella et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also within the translocation domain are a hairpin loop between β-strands 5 and 6 (the β5-6 hairpin), which dips toward the barrel lumen, and the only α-helix in the translocation domain, which caps the β5-6 hairpin from the extracellular side. These two elements are believed to confer stability to the surrounding region, particularly to the plug domain, as their removal causes increased pore permeability (Volkan et al, 2013), channel opening (Mapingire et al, 2009) and decreased interactions between conserved residues (Farabella et al, 2014). Specific communities of amino acids in the α-helix and the β5-6 hairpin were proposed to function in the transmission of a putative allosteric signal that triggers plug displacement (Farabella et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The pilus is a critical virulence factor in mediating the attachment and invasion of bacteria into host cells, while the flagellum is mainly responsible for cell motility. It has been reported that some pilus proteins could negatively regulate the expression of flagellar proteins and the process of flagellar biosynthesis (40)(41)(42). In Vibrio species, FlhG is a typical pilus assembly protein with a function as an antiactivator for flagellar biosynthesis, and its high expression would impact the synthesis of the flagellum (43).…”
Section: Discussionmentioning
confidence: 99%
“…After translocation into the periplasmic space, the PD mediates a high-affinity interaction with the NTD of the usher (41, 44). Thus, the PD gates the translocation domain such that, in the absence of pili, the PD prevents large molecules from flowing freely across the outer membrane (45). The PD, NTD, CTD1, and CTD2 work together in the assembly function of this molecular machine.…”
Section: Chaperone Usher Pathway (Cup) Pilimentioning
confidence: 99%
“…(45,(47)(48)(49). Pilus DSE occurs at the usher when the chaperone is displaced, and an incoming subunit's N-terminal extension zips into the previously chaperone-bound groove of a nascently incorporated subunit at the growing terminus of the pilus (Fig.…”
Section: Chaperone Usher Pathway (Cup) Pilimentioning
confidence: 99%